Análise populacional de melolonthidae (Coleoptera) da região do planalto do Rio Grande do Sul - Cherman, Mariana Alejandra (2011)
This work aimed to study the occurrence of soil-dwelling melolontid species called white grubs (Coleoptera: Melolonthidae) and its geographic distribution in Planalto , Rio Grande do Sul State. Chapter I, describes the current species at larva and adult stadium, provides a taxa key for regional identification and characterizes geographic species distribution. Chapter II analyzes white grubs diversity and populational density in each wild and crop fields and the relation between pest and no-pest communities. Surveys were carried out during both winter 2009 and 2010 in 23 localities distributed in Planalto region. Samplings were made in crop and wild fields in every locality. Population density was estimated with the larvae collected from soil trenches and taxa identification was confirmed by the observation of taxonomic features. For geographic distribution characterization, CRIA Species Link System was used. Community characterization was carried out through diversity and equitability faunistic indexes, and through abundance, frequency, constancy and dominance parameters. For populational density comparations, bootstrap T- test were used. There were found 28 melolontid species, which nine of them are already cited for RS. D. abderus and C. flavipennis were the most abundant and current species. Richness is concentrated in northeast and in Planalto Médio region. White grubs abundance was higher in crop fields, but wild fields were more diverse. The community of no-pest species is larger than the pest one in every field, and there were no differences on populational density of pest and no pest species between crop and wild fields.